Recalling the language skills of children with childhood disintegrative disorder (CDD) - Rosyidi, Rizky Amalia; Efendi, Mohammad; Sunandar, Asep (Jurnal Cakrawala Pendidikan, 2025)
This study aimed to examine the effectiveness of Discrete Trial Training (DTT) intervention in restoring expressive language abilities in a child diagnosed with Childhood Disintegrative Disorder (CDD), a rare neurodevelopmental condition. Recalling language behavior in children with CDD is essential to understanding regression and potential recovery mechanisms. A single-subject experimental method using an A1-B-A2 design was applied, involving three phases: initial baseline (A1), intervention (B), and follow-up baseline (A2). The subject was a 5-year-old child who experienced severe language and behavioral regression. Language skills were assessed through observation sessions and analyzed descriptively using intra- and inter-condition comparisons. The intervention phase consisted of ten DTT sessions focusing on attention, matching, identification, imitation, and labeling skills. The findings demonstrated positive, consistent improvements in expressive language behavior, with trends showing increased scores and stable performance across phases. Notably, the overlap in data between conditions was 0%, indicating a high level of intervention effectiveness. The results also showed behavioral generalization post-intervention, with increased engagement and adaptive functioning. This study concludes that DTT is an effective intervention for recalling expressive language skills in children with CDD. The improvement was marked not only by the return of verbal abilities but also by gains in behavioral regulation and social interaction. Further research involving larger populations and long-term monitoring is recommended to generalize findings and enhance intervention strategies for CDD.